2015
DOI: 10.1111/ajgw.12133
|View full text |Cite
|
Sign up to set email alerts
|

Sensory interaction between 3-mercaptohexan-1-ol, 3-isobutyl-2-methoxypyrazine and oxidation-related compounds

Abstract: Background and Aims:Wine aroma is influenced by complex interactions between various wine constituents. This study investigated the sensorial interactive effects of Sauvignon Blanc impact compounds, 3-mercaptohexan-1-ol, 3-isobutyl-2-methoxypyrazine with aldehydes typically originating from oxidation of white wines, methional and phenylacetaldehyde. Methods and Results: Spiked model wines were subjected to sensory descriptive analysis using a trained panel. The concentration of each compound varied from below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 46 publications
1
30
1
Order By: Relevance
“…Surprisingly, a weak correlation (r 2 = 0.37) was obtained when comparing IBMP concentration with the aromatic intensity of the "capsicum" attribute (Lund et al, 2009b). The contribution of other aromatic compounds, such as the varietal thiols, C6-alcohols and dimethyl sulphide, to these types of attributes can be significant in Sauvignon blanc wines and help explain the weak correlation observed previously (Park et al, 1994;Marais et al, 1998;Lund et al, 2009b;King et al, 2011;Van Wyngaard, 2013;Coetzee et al, 2015a).…”
Section: Methoxypyrazinesmentioning
confidence: 81%
See 2 more Smart Citations
“…Surprisingly, a weak correlation (r 2 = 0.37) was obtained when comparing IBMP concentration with the aromatic intensity of the "capsicum" attribute (Lund et al, 2009b). The contribution of other aromatic compounds, such as the varietal thiols, C6-alcohols and dimethyl sulphide, to these types of attributes can be significant in Sauvignon blanc wines and help explain the weak correlation observed previously (Park et al, 1994;Marais et al, 1998;Lund et al, 2009b;King et al, 2011;Van Wyngaard, 2013;Coetzee et al, 2015a).…”
Section: Methoxypyrazinesmentioning
confidence: 81%
“…Descriptive analysis has been used successfully as a tool to differentiate between Sauvignon blanc wines from different vintages and countries (Lund et al, 2009b;Green et al, 2011). These techniques have also been used to investigate interactions between various compounds in Sauvignon blanc wine (King et al, 2011;Benkwitz et al, 2012a;Coetzee et al, 2015a;2015b), as well as to identify off-flavours in oxidation-spoiled white wines (Silva Ferreira et al, 2003b).…”
Section: Other Carbonyl Compounds and Acetalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aroma compounds in wine are perceived together, and different combinations could have olfactory impact even when they are present at peri-threshold or subthreshold levels (Lorrain, et al, 2013). Recent research has shown that aroma compounds such as thiols produce aromatic differences in wine when they are present in combination (Coetzee et al, 2015, Lapalus et al, 2016Wilson, et al, 2018), which suggests that malodourous compounds in combination at peri-and sub-threshold levels in wine might also produce variable aromatic effects. Chemical assessment of the sensory impact of compounds in wines generally consider the ODT or OAV (odour activity value) of individual compounds, and disregard or overlook the combinatorial effects of all the compounds in solution, including the matrix effect.…”
Section: Introductionmentioning
confidence: 99%
“…Aroma can induce flavor sensations and can be used to identify compounds that might aid in the development of higher quality wines (Coetzee et al, 2015;Welke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%